Effectiveness Trial of an Indicated Cognitive-Behavioral Group Adolescent Depression Prevention Program versus Bibliotherapy and Brochure Control at 1- and 2-Year Follow-Up - Rohde, Paul (J Consult Clin Psychol, 2015)
OBJECTIVE: Evaluate the longterm effects of a brief group cognitive-behavioral (CB) adolescent depression indicated prevention program through 2-year follow-up, relative to CB bibliotherapy and brochure control, when high school personnel recruited students and delivered the program. METHOD: 378 adolescents (M age = 15.5, SD = 1.2; 68% female, 72% White) with elevated self-assessed depressive symptoms who were randomized to CB group, CB bibliotherapy, or educational brochure control were assessed at pre, post, 6-, 12-, 18-, and 24-month follow-up. RESULTS: By 2 years post-intervention, CB group participants showed significantly lower major depressive disorder (MDD) onset versus CB bibliotherapy (10% vs. 25%, respectively; HR = 2.48, p = .006), but the incidence difference relative to brochure controls (17%) was nonsignificant; MDD incidence for bibliotherapy and brochure controls did not differ. Although CB group participants showed lower depressive symptoms at post versus brochure controls, there were no effects for this outcome or for social adjustment or substance use over 2-year follow-up. Moderator analyses suggested that participants with higher baseline depressive symptoms showed greater longterm symptom reductions in the CB group intervention versus bibliotherapy. CONCLUSIONS: The evidence that a brief CB group intervention delivered by real-world providers significantly reduced MDD onset versus CB bibliotherapy is potentially encouraging. However, the lack of MDD prevention effects relative to brochure control and lack of longterm symptom effects (though consistent with results from other depression prevention trials), suggest that the delivery of CB group should be refined to strengthen its effectiveness.